Substitusi Medium Sintetik dengan Pupuk Daun, Air Kelapa dan Ekstrak Nabati pada Subkultur Anggrek Cattleya pastoral Innocence secara In Vitro - Etty Handayani; Bambang Heri Isnawan (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2014)
A research was perfomed to find the proper of coconut water and natural ekstracts combined with Hyponex medium that compared with Vacin Went medium. This research has been done at Tissue Culture Laboratory, Agricultural Faculty, Universitas Muhammadiyah Yogyakarta. The method of this research was arranged in Randomized Complete Design with 9 treatments and 8 replications. The treatments were VW + NAA 0,5 ppm + BAP 3 ppm, green Hyponex 3 g/l, green Hyponex 3 g/l + bean sprouts 150 g/l, green Hyponex 3 g/l + tomatoes 150 ml/l, green Hyponex 3 g/l + avocado 150 g/l, red Hyponex 3 g/l, red Hyponex 3 g/l + bean sprouts 150 g/l, red Hyponex 3 g/l + tomatoes 150 ml/l, red Hyponex 3 g/l + avocado 150 g/l. The each of Hyponex mediums were given with bananas 150 g/l and coconut water 150 ml/l. The result of this research showed that Hyponex mediums combined with natural ekstract was not signicicantly with Vacin Went medium to high and shoot growth. Red Hyponex medium 3 g/l combined bananas 150 g/l and coconut water 150 ml/l resulted the best high, leaf and shoot in tissue culture Cattleya pastoral innocence orchid.